Iodine nutrition and papillary thyroid cancer - Zhang, Xueqi; Zhang, Fan; Li, Qiuxian; Feng, Chuyao; Teng, Weiping (Frontiers in Nutrition, 2022)
Thyroid cancer (TC) is the most frequent endocrine malignancy. The incidence of TC, especially papillary thyroid carcinoma (PTC), has continued to rise all over the world during the past few years, for reasons that are not entirely clear. Though the phenomenon of overdiagnosis is occurring, it is not the sole driver of the substantial increase in incidence. Lifestyle, environmental factors, or complications are considered to be potential risk factors. Among these factors, iodine is a micronutrient that is vital to thyroid function. The effect of iodine intake on PTC has been controversial for many years and the epidemiological or experimental studies provided diametrically opposite conclusions. Combining all these studies, we found that iodine nutrition may affect the overall prevalence, distribution of the histological types, and clinicopathological aggressiveness of TC, especially PTC. However, the available evidence is poor due to the impact of various internal and external related factors. Therefore, this article sums up available results from both epidemiological and experimental studies, future studies are also warranted to expound on the relationship between overall PTC prevalence and iodine intake.